Light touch compensates peripheral somatosensory degradation in postural control of older adults - Barela, Ana M. F.; Caporicci, Sarah; Freitas, Paulo Barbosa de; Jeka, John J.; Barela, Jose A. [UNESP] (Elsevier B.V., 2018)
The present study aimed to investigate the sensitivity of detecting lower limb passive motion and use of additional sensory information from fingertip light touch for the postural control of older adults in comparison with young adults. A total of 11 older and 11 young adults (aged 68.1 +/- 5.2 and 24.2 +/- 2.2 years, respectively) underwent two tasks. We evaluated their sensitivity to passive ankle joint movement while seated in the first task. Participants then stood quietly on a force plate in a semi-tandem stance, for 30 s under two fingertip contact force conditions (no touch and light touch limited to 1 N). The results showed that the threshold of passive ankle displacement and body sway is higher in older adults than in young adults. The body sway reduced for both older and young adults with the addition of light touch at the fingertips. The maximum cross-correlation coefficient and time lags between body sway and fingertip light touch center of pressure was similar between both groups, suggesting that older adults used light touch to reduce body sway, similar to young adults. A higher threshold in detecting passive ankle joint movement may contribute to the increased body sway observed in older adults. These deficits may be compensated by additional sensory cues that would provide enhanced information used to control the upright stance.
Keywords: Body sway; Light touch fingertip; Passive joint movement; Proprioception